SP0085 Music and rheumatism. (1st June 2001) - Grassi, W; De Angelis, R; Farina, A; Cervini, C
Abstract : The relationship between music and rheumatism is strong, complex, and interesting. It can be classified into five general categories: Occupation-specific musculoskeletal diseases in musicians due to repetitive strain injury; Joint hypermobility-related benefits among musicians; Joint hypermobility-related disadvantages among musicians; Rheumatological pathography of famous composers (e.g., Beethoven, Schumann, Paganini); Joint music (acoustical analysis of joint sounds by digital phonoarthrometry); Music therapy for pain and anxiety management. Musculoskeletal symptoms are highly prevalent among musicians at all levels of performance. 1 This is not surprising in the context of activities involving repetitious movement and/or postural constraint. Increased tension in the affected muscles could play an important causative role. Playing-related musculoskeletal disorders in musicians (PRMD) are chronic and disabling conditions that may lead to the loss of a career and incomes because of the weakness of the executant muscle actions and loss of agility, speed and accuracy. PRMD are also under-recognised and under-researched causes of pain and disability especially in music students. Data from previous surveys indicate that the prevalence of PMRD in adult classical musicians is comparable to the prevalence of work-related musculoskeletal disorders reported for other occupational groups. Clinical findings of PMRD are deeply related to size, weight, playing position of the instrument, playing time, posture, and technique. Soft tissue rheumatism and predisposition to injury are common associations of joint hypermobility among musicians. 2 However, joint hyperlaxity may confer advantages in playing some instruments such as flute, piano, and violin. 3 The outstanding virtuosity of the violinist Niccolò Paganini has been related to the remarkable laxity of his joints. Hand pain is a very common complaint among classical musicians. Clinical syndromes include: piano and guitar cramp, traumatic synovitis of the wrist joint, dystonia, carpal tunnel syndrome, acro-osteolysis, ulnar neuropathy and premature closure of the growth of the fingers in adolescents. The onset of clinical features is generally associated with an increase in playing or practice load. Hand difficulties are more frequent among pianists. They include: pain, weakness, tightening, cramping, curling and drooping, and loss of control. The diagnosis of PRMD can be difficult when symptoms are mild and only occur on playing. The management of PMRD is often difficult. Early and regular prevention, rest, splinting, correction of technical problems by skilled teachers of the instrument, and ergonomic redesign of some instruments can be of critical importance. Non steroidal anti-inflammatory drugs and local steroid injection can provide good symptomatic relief. Occupational therapy can be very useful. 4 Trills, arpeggios or octaves should be avoided or reduced in pianists with hand complaints. Some composers such as Tchaikowsky (Piano Concerto N. 1 in B-flat Minor) or Beethoven (Piano Concerto N. 3 in C Minor; Sonata in E Major, opus 109; Sonata in C Major, opus 2 N. 3) seem to be at higher risk of worsening hand pain and inability. 5 Music therapy as a treatment for chronic pain disorders and for depression has been proposed. References: Zaza C. Playing-related musculoskeletal disorders in musicians: a systematic review of incidence and prevalence. CMAJ 1998;158:1019–25 Fry HJH. Overuse syndrome in musicians: prevention and management. Lancet 1986;ii:728–31 Grahame R. Joint hypermobility and the performing musician. N Engl J Med. 1993;329:1120–1 Hochberg FH, Leffert RD, Heller MD, Merriman L. Hand difficulties among musicians. JAMA 1983;249:1869–72 Cervini C, Gasparini M, Grassi W. La "sindrome da bandoneòn". Proceedings of the XXVII Congresso Nazionale della Società Italiana di Reumatologia. Montecatini Terme, 30 October–2 November 1986. Abstract no. 172